2015
DOI: 10.1002/chem.201405858
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Discrimination of Carboxylates by Hydrogen‐Bond Donor Anion Receptors

Abstract: The binding constants (log Kass ) of small synthetic receptor molecules based on indolocarbazole, carbazole, indole, urea and some others, as well as their combinations were measured for small carboxylate anions of different basicity, hydrophilicity and steric demands, that is, trimethylacetate, acetate, benzoate and lactate, in 0.5 % H2 O/[D6 ]DMSO by using the relative NMR-based measurement method. As a result, four separate binding affinity scales (ladders) including thirty-eight receptors were obtained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…K a in [D 6 ]DMSO (0.5 % water) at 298 K (estimated error in K a <15 %). [e] Value from reference . K a in [D 6 ]DMSO (0.5 % water) at 298 K (error in K a ±18 %).…”
Section: Resultsmentioning
confidence: 99%
“…K a in [D 6 ]DMSO (0.5 % water) at 298 K (estimated error in K a <15 %). [e] Value from reference . K a in [D 6 ]DMSO (0.5 % water) at 298 K (error in K a ±18 %).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the compounds 1 H 2 and 4 H 2 have been included in a previous study reported by Gale et al., and their anion binding (1:1 complex stoichiometry) was characterized by 1 H NMR titrations in DMSO containing 0.5 % water. Most recently, Gunnlaugsson et al.…”
Section: Resultsmentioning
confidence: 99%
“…In this field, urea derivatives have been among the most studied receptors, and numerous studies of their complexation with diverse anionic species have been reported . In pursuit of higher affinity and selectivity, original concepts have been examined with the goal of achieving the desired receptor properties . A prerequisite facilitating the anion receptor development is comprehensive understanding of the thermodynamics underlying anion binding, leading to appreciation of structure–reactivity correlation, assessment of the individual contributions to the complex stability, better insight into the solvent effect on the corresponding equilibria, etc .…”
Section: Introductionmentioning
confidence: 99%
“…The summary of experimental results is presented in Scheme . The anion–receptor complex structures with receptors 8 , 10 , 11 and 15 have been computed for all 11 anions (complexes between 8 , 11 , 15 and lactate, benzoate, acetate, and pivalate are available from ref …”
Section: Resultsmentioning
confidence: 99%
“…Receptor Molecules: Receptors 1 – 6 , 8 , 11 , 14 – 16 are the same as used in ref., 17 – 19 , 22 are from ref., and 20 , 21 from ref . Synthesis procedures of compounds 9 and 10 are described in ref .…”
Section: Methodsmentioning
confidence: 99%